Culturomics Reveals Microbial Dynamics in the Apple Carposphere Across Developmental Stages, Altitude and Tissue Types - Ana María Sánchez; Jonàs Oliva; Cristina Solsona; Ahmed Abdelfattah; Neus Teixidó (Journal of Sustainable Agriculture and Environment)
ABSTRACT The apple carposphere harbours a diverse community of microorganisms that could play a crucial role in fruit health and postharvest preservation. While culture‐independent techniques have advanced our understanding of the apple microbiome, a substantial portion of this community remains unexplored due to cultivation limitations. In this study, a culturomics approach was adopted using culture media enriched with apple‐derived nutrients to recover and characterise the epiphytic and endophytic bacterial and fungal communities of apple fruits. Aiming to analyse the effects of the altitude and developmental stage of the fruit on these microbial communities. To do this, the impact of altitude (Pyrenees mountain vs. Ebro valley), fruit developmental stage (30 days before harvest vs. harvest) and tissue type (epiphytes vs. endophytes) was assessed on microbial diversity and composition across four orchards in Catalonia, Spain. Using 13 distinct culture media, 50% more microbial genera were recovered than conventional laboratory media, yielding over 919 isolates, consisting of 489 bacteria, 222 filamentous fungi and 208 yeasts. The results showed that altitude, developmental stage and type of culture media influenced microbial diversity and composition. Richness of endophytic fungi was more influenced by altitude and developmental stage than epiphytic fungal and bacterial communities. On the other hand, bacterial community composition was strongly influenced by the type of culture medium used. Functional characterisation of isolates revealed potential biocontrol agents and plant pathogens, with some genera displaying altitude‐specific distributions. Our findings demonstrate that culturomics provides an essential tool to unlock the hidden diversity of fruit‐associated microbiomes, paving the way for future applications in sustainable agriculture and postharvest disease management.